Overexpression of microRNA-202-3p protects against myocardial ischemia-reperfusion injury through activation of TGF-β1/Smads signaling pathway by targeting TRPM6. Issue 5 (4th March 2019) - Wu, Hui-Ying; Wu, Jian-Li; Ni, Zhan-Ling
ABSTRACT: MicroRNAs (miRNAs) have been found to act as key regulators in the pathogenesis of myocardial ischemic-reperfusion (I/R) injury. In this study, we explore the role and mechanism of microRNA-202-3p (miR-202-3p) in regulating cardiomyocyte apoptosis, in respective of the TGF-β1/Smads signaling pathway by targeting the transient receptor potential cation channel, subfamily M, member 6 (TRPM6). The targeting relationship between miR-202-3p and TRPM6 was verified by a dual-luciferase reporter gene assay. Sprague-Dawley rat models of myocardial I/R injury were initially established and treated with different mimics, inhibitors and siRNAs to test the effects of miR-202-3p and TRPM6 on myocardial I/R injury. The levels of inflammatory factors; IL-1β, IL-6, TNF-α as well as the degree of myocardial fibrosis and cardiomyocyte apoptosis were determined in rats transfected with different plasmids. TRPM6 was found to be the target of miR-202-3p. Up-regulated miR-202-3p or knockdown of TRPM-6 alleviated oxidative stress and inflammatory response, reduced ventricular mass, altered cardiac hemodynamics, suppressed myocardial infarction, attenuated cell apoptosis, and inhibited myocardial fibrosis. MiR-202-3p overexpression activates the TGF-β1/Smads signaling pathway by negatively regulating TRPM6 expression. Taken together, these findings suggest that miR-202-3p offers protection against ventricular remodeling after myocardial I/R injury via activation of the TGF-β1/Smads signaling pathway.